SYNTACTIC STRATEGIES IN TRANSLATING AND ANALYZING ENGLISH MECHANICAL ENGINEERING TERMS INTO INDONESIAN - Brillianta, Cintania Dharma; Yoga, Damar Putra (Journal of Language and Literature, 2024)
This study reports the syntactic strategies used in translating mechanical engineering terms in the The Martian novel and its translation. The objective of this study is to find out what syntactic strategies are used by the translator in translating English mechanical engineering terms to Indonesian in The Martian novel. This study used the descriptive qualitative method. Meanwhile, the approach used in the study is descriptive analytical. The data of this study are in the forms of words and clauses reflecting the mechanical engineering terms. The writers used the theory of translation strategies from Chesterman. The writers only focus on observing syntactic translation strategies. The results of this study show that from the 21 data analyzed, the syntactic strategies used were literal translation (10 data), calque (7 data), loan (3 data), and unit shift (1 datum). The less dominant syntactic strategy is the unit shift with only one datum. Meanwhile, the most dominant syntactic strategy used by the translator in translating The Martian novel is literal translation.